2011
DOI: 10.1017/s0950268811000598
|View full text |Cite
|
Sign up to set email alerts
|

Changes in measles seroepidemiology of healthcare workers in southern Taiwan

Abstract: To assess the measles seroepidemiology of healthcare workers (HCWs), from 2004 to 2009 all newly recruited staff at a university hospital in Taiwan, were tested for specific immunoglobulin G antibodies for measles virus using enzyme-linked immunosorbent assays. A total of 1584 HCWs were included. The positivity rate of measles antibody for physicians and nurses was about 90%. The positivity of measles antibody in different age groups was 78·1%, 93·9% and 94·2% for 20-29, 30-39 and ≥40 years age groups, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…In Asia and the Western Pacific, studies published between 1994–2012 found 1.7%- 18.9% (median 10.3%) of healthcare personnel had negative measles titers [6673] with younger age groups at higher risk for being measles seronegative [67, 68, 7072]. Studies from the Middle East published between 2005–2012 found a median proportion of healthcare personnel who were seronegative of 9.2%, with seronegativity ranging from 1.4% in a study of healthcare staff in Turkey to 46% in medical students in United Arab Emirates [7482].…”
Section: Resultsmentioning
confidence: 99%
“…In Asia and the Western Pacific, studies published between 1994–2012 found 1.7%- 18.9% (median 10.3%) of healthcare personnel had negative measles titers [6673] with younger age groups at higher risk for being measles seronegative [67, 68, 7072]. Studies from the Middle East published between 2005–2012 found a median proportion of healthcare personnel who were seronegative of 9.2%, with seronegativity ranging from 1.4% in a study of healthcare staff in Turkey to 46% in medical students in United Arab Emirates [7482].…”
Section: Resultsmentioning
confidence: 99%
“…Before hospitalization of all children younger than 12 months in the hospital setting of high risk for complications of measles, vaccination of unvaccinated mothers or those without the proof of measles IgG seropositivity was recommended also. Furthermore, vaccination with one dose of MMR vaccine was required for all unvaccinated or partly vaccinated medical students involved in hospital practice [50].…”
Section: Discussionmentioning
confidence: 99%
“…Measles antibody positivity was 74.7% in Taiwan [21], 80% in Japan [25] and 85.8% at baseline in this study. In a study conducted between 2004 and 2009 on health care workers at a hospital in southern Taiwan, Ho et al found that measles antibody positivity was 78.1% for the age group 20–29 years [26]. However, measles seropositivity for the age group 20–29 years in first-line medical personnel in our hospital in 2018 was even lower than reported by Ho et al…”
Section: Discussionmentioning
confidence: 63%